APRESIASI MASYARAKAT JORONG GUGUAK TERHADAP TARI BATU BARAJUIK - Mery Susanti; Yuliasma Yuliasma; Susmiarti Susmiarti (SENDRATASIK UNP, 2015)
Abstract   This article aims to reveal and explain the level of public appreciation of the existence of dance Stone Barajuik in Jorong Guguak Pariangan Tanah Datar. This research is a qualitative descriptive method. Data were obtained by direct observation and interviews, as well as literature and documentation. Data were analyzed based on the phenomenon that occurs on the existence of Stone Barajuik and appreciation of dance in the dance community, using the model of Miles and Huberman. The results showed, that the public recognition of the dance Stone Barajuik very less, so the art of dance Stone Barajuik be marginalized by society itself in Jorong Guguak today. The level of public appreciation of the existence of dance Stone Barajuik found to be low. people do not know and understand the ins and outs, and philosophy or aesthetics of dance Stone Barajuik, therefore people do not appreciate the Stone Barajuik dance well. The issue also lies in the closure of the heir to the community, so that people do not fully know the dance. Keywords: appreciation society, and batu barajuik dance.